Conocimientos sobre el manejo de enfermedades respiratorias agudas en madres de niños menores de cinco años, usuarias del Subcentro de Salud Santa Clara, Provincia De Pastaza. Año 2013 -2014 - Lucero Lucero, Rosa Guillermina (2015)
The need arises to conduct this research in order to determine the level of knowledge on the management of acute respiratory diseases in mothers of children under 5 years of age, due that it was shown that these conditions were the main cause of pediatric consultations at the Subcenter health of Santa Clara, with most recurrent cases, in order to enable them to make immediate achieve home care, danger signs detected if present and prevent children from reaching a state of complication. The research design was cross-sectional, descriptive, and bibliographic and field fixed, the technique used was a survey that was applied to 45 mothers and observation guides for review of medical records. As a result it was found that 40% of mothers are teenagers, 53% have a low level of knowledge about the disease among the most important risk factors for the presence of smokers in the household was determined with 47 % only 24% of children have a varied diet and 58 % have recurrent respiratory problems. it was determined a significant number of mothers are teenagers, they do not know about respiratory disease and feeding children is poor, for which a training plan was designed with the aim to increase knowledge of mothers on the management of this pathology. The research process was among one year KEYWORDS: Acute respiratory diseases, Children under 5 years, Knowledge